The Long Telling Story of “Endothelial Progenitor Cells”: Where Are We at Now? - Maria Cristina Vinci; Ermes Carulli; Erica Rurali; Raffaella Rinaldi; Giulia Damiano; Angela Raucci; Giulio Pompilio; Stefano Genovese (Cells, 2022)
Endothelial progenitor cells (EPCs): The name embodies years of research and clinical expectations, but where are we now? Do these cells really represent the El Dorado of regenerative medicine? Here, past and recent literature about this eclectic, still unknown and therefore fascinating cell population will be discussed. This review will take the reader through a temporal journey that, from the first discovery, will pass through years of research devoted to attempts at their definition and understanding their biology in health and disease, ending with the most recent evidence about their pathobiological role in cardiovascular disease and their recent applications in regenerative medicine.